2005
DOI: 10.1001/archinte.165.14.1582
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of a Testosterone Patch for the Treatment of Hypoactive Sexual Desire Disorder in Surgically Menopausal Women

Abstract: The 300-microg/d testosterone patch increased sexual desire and frequency of satisfying sexual activity and was well tolerated in women who developed hypoactive sexual desire disorder after surgical menopause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
2
8

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 414 publications
(107 citation statements)
references
References 21 publications
3
94
2
8
Order By: Relevance
“…Goldstat et al reported that application of testosterone cream for 12 weeks improved well-being, mood, and sexual function without any adverse effects in premenopausal women with low libido and low testosterone level (63). It has been reported that transdermal testosterone at a dose of 300 μg/day was effective for sexual desire in surgically and naturally menopausal women (64) and in women with hypoactive sexual desire disorder after surgically induced menopause (65,66) (68). The results of Cochrane Review meta-analysis showed that hormone therapy (HT) plus testosterone improved libido, sexual function and sexual activity compared to the effects of HT alone (69).…”
Section: Supplementation Of Testosterone and Dhea-s In Womenmentioning
confidence: 99%
“…Goldstat et al reported that application of testosterone cream for 12 weeks improved well-being, mood, and sexual function without any adverse effects in premenopausal women with low libido and low testosterone level (63). It has been reported that transdermal testosterone at a dose of 300 μg/day was effective for sexual desire in surgically and naturally menopausal women (64) and in women with hypoactive sexual desire disorder after surgically induced menopause (65,66) (68). The results of Cochrane Review meta-analysis showed that hormone therapy (HT) plus testosterone improved libido, sexual function and sexual activity compared to the effects of HT alone (69).…”
Section: Supplementation Of Testosterone and Dhea-s In Womenmentioning
confidence: 99%
“…Entretanto, vários ensaios clínicos controlados realizados em mulheres na pós-menopausa, associados à TE ou à TEP, acumulam evidências do benefício da testosterona sobre o desejo, a responsividade e a freqüência da atividade sexual (Shifren et al, 2000;Floter et al, 2002;Lobo et al, 2003;Braunstein et al, 2005;Buster et al, 2005).…”
Section: O Tratamento Com Estrogênios E Androgêniosunclassified
“…Entretanto, a mais estudada tem sido a transdérmica, uma vez que a pele absorve bem a testosterona. Em que pese a falta de estudos clínicos conclusivos, a administração através de adesivos ou de formulações em gel transdérmico, nas doses diárias de 150 a 300 mcg, tem mostrado bons resultados sobre a sexualidade feminina, incluindo a melhora do desejo, da freqüência, da satisfação e da atividade sexual em mulheres na pós-menopausa (Braunstein et al, 2005) (Figura 5).…”
Section: Como Empregar Os Androgêniosunclassified
See 1 more Smart Citation
“…Distressing sexual disorders are more frequently reported in women with PM [4,34], particularly after bilateral oophorectomy. A recently published randomised placebo controlled trial was conducted in surgically menopausal women (aged 24-70) who developed stressful hypoactive sexual desire disorder [35]. Treatment with 300-µg/d testosterone patches on estrogen repleted women increased sexual desire and frequency of satisfying sexual activity and were well tolerated [35].…”
Section: Premature Menopausementioning
confidence: 99%